2005
DOI: 10.1177/1524839903260846
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of an Interactive Small Group Diabetes Intervention in Improving Knowledge, Feeling of Control, and Behavior

Abstract: The objective of this study is to evaluate the effectiveness of a small group intervention in improving knowledge, feeling of control, and behaviors related to self-management of diabetes. The intervention includes educational content on diabetes self-management as well as discussion of attitudes, feelings, and motivations about living with diabetes. The authors randomized volunteers into an intervention group that participated in the small-group learning activity and a control group that received a diabetes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…The content areas are designed to be applicable in all settings and represent topics that can be developed in basic, intermediate, and advanced levels. Approaches to education that are interactive and patient-centered have been shown to be effective (83,119,121,122,125127). …”
Section: Standardsmentioning
confidence: 99%
“…The content areas are designed to be applicable in all settings and represent topics that can be developed in basic, intermediate, and advanced levels. Approaches to education that are interactive and patient-centered have been shown to be effective (83,119,121,122,125127). …”
Section: Standardsmentioning
confidence: 99%
“…The content areas are designed to be applicable in all settings and represent topics that can be developed in basic, intermediate, and advanced levels. Approaches to education that are interactive and patient-centered have been shown to be effective (83,119,121,122,125127). …”
Section: Standardsmentioning
confidence: 99%
“…8 The struggle associated with management of nutrition, medication, exercise, and stress management, and the multiple social factors involved are consistent with the findings of previous studies. 7,11,12 In addition, these educators are fulfilling the mission of the AADE Position Statement and linking these patients with the personal services they need to manage their health needs regarding diabetes. 6 Diabetes education is a key component of the self-management of diabetes, [13][14][15][16][17] and additional diabetes educators will be needed in the future with the increasing numbers of persons diagnosed with diabetes.…”
Section: Resultsmentioning
confidence: 98%
“…Research has found that interventions need to address not only knowledge of diabetes but also attitudes and motivation; improving attitudes has been shown to have a positive effect on diabetes management. 7 Evidence to support the important role of the diabetes educators' values and interpersonal skills and their ability to establish a therapeutic alliance with patients is lacking in the literature. 8 Therefore, the purpose of this study was to understand the teaching experiences of persons teaching in a rural diabetes program.…”
mentioning
confidence: 99%